Measurement Validation of Service Ethics Higher Education in Indonesia - Rusyani, Erni; Kurniatun, Taufani Chusnul; Arifin, Yusuf (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
This study aims to develop an ethics index of education services at universities in Indonesia with an approach to marketing education services. This is because service ethics is a long-term investment to build trust by providing services that can create ethical education. This research was calculated using the â€œweighted average valueâ€ of each indicator of service ethics, with a population of students from State and Private Universities in Banjarmasin and Makassar. Based on findings obtained from two major groups of the University, namely Higher Education in the City of Banjarmasin and Higher Education in the City of Makassar, the University has a Good Higher Education Ethics Performance (KEPT). Each University, whether Higher Education in Banjarmasin City or Higher Education in Makassar City has different characteristics, for Higher Education in Banjarmasin and Makassar City have similarities with the highest aspects in the Education Service Ethics Index in Higher Education, namely Lecturers provide opportunities for students to apply the lowest questions and aspects, namely the campus building does not provide facilities for students with disabilities or special needs (there are no block or road markers, there are toilets for people with disabilities, names or room numbers using braille).